Effect of Tillage Techniques on Depth, Furrow Slice and Water Retention in Maugo Smallholder Rice Scheme in Kenya - Pius Kipchumba Cheboi; Clement Kiprotich Kiptum; Japheth O. Onyando (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted with the aim of determining the influence of tillage techniques on depth, furrow slice and water retention in Maugo Smallholder Rice Scheme in Kenya. Treatments were arranged in randomized complete block design with four replicates. Four tillage treatments were used. The first one was conventional ox plough practiced by farmers where they first flood the field with water before ploughing. The other three treatments were ox plough, hand hoe and tractor ploughing all with no flooding before ploughing. Data collected included depth of ploughing and harrowing during land preparation. Furrow slices during ploughing and harrowing as well as water retention were recorded. Tractor ploughing had the highest mean depth of ploughing of 42.00 ± 0.81 cm followed by conventional ox ploughing with 17.75 ± 0.75 cm, ox ploughing15.75 ± 0.62 cm and hand hoe ploughing had the lowest mean depth 15.50 ± 0.28 cm. Tractor ploughing had the largest mean furrow size of 62.00 ± 0.91cm followed by conventional ox ploughing 32.25 ± 0.85 cm, ox ploughing 30.25 ± 0.85 cm while hand hoe ploughing had the smallest mean furrow slice of 16.5 ± 0.50 cm. Highest mean of retained water was recorded in week 4 in paddy rice fields prepared using conventional ox ploughing (10.5 cm), ox ploughing (10 cm), hand hoe ploughing (11.5 cm) and tractor ploughing (11.5 cm) while the lowest was recorded in week 15 for conventional plots. There were significant differences in mean depths during both ploughing and harrowing. Tractor ploughing mean depths were significantly different from the other treatments. The weekly mean water depths retained in the plots were more than 6 cm for the entire growing period of rice.